The Validity of The Sale And Purchase Deed Was Not Signed in The Presence of Land Deed Officer - Titis Giriarti; Tri Lisiani Prihatinah; Sri Wahyu Handayani (Jurnal Hukum dan Kenotariatan, 2023)
The sale and purchase deed is proof that the sale and purchase process has been carried out regarding land rights or ownership rights to apartment units made by land deed officer. In making sale and purchase deed is must be attended by the parties carrying out the legal action concerned or their authorized person and land deed officer. The problem raised in this research is the validity of the sale and purchase deed whose signing was not in the presence the land deed officer. The research aims to analyze the validity of deeds of sale not executed in the presence of a land deed officer and the responsibility of the land deed officer towards the aggrieved party in making such deeds. Deeds of sale that are not executed in the presence of a land deed officer are considered illegitimate because they fail to satisfy both the formal criteria. The responsibility of the land deed officer towards the aggrieved party regarding the making of deeds of sale takes the form of civil liability, responsible to compensate for the damages caused by their fault and materially compensate for the losses suffered